2016
DOI: 10.1093/brain/aww218
|View full text |Cite
|
Sign up to set email alerts
|

Variable disruption of a syntactic processing network in primary progressive aphasia

Abstract: Syntactic processing deficits are highly variable in individuals with primary progressive aphasia. Damage to left inferior frontal cortex has been associated with syntactic deficits in primary progressive aphasia in a number of structural and functional neuroimaging studies. However, a contrasting picture of a broader syntactic network has emerged from neuropsychological studies in other aphasic cohorts, and functional imaging studies in healthy controls. To reconcile these findings, we used functional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 78 publications
5
34
1
Order By: Relevance
“…Yet, along-side many of the findings just reviewed, our results stand in contrast to the apparent stability of compositional processes following anterior temporal atrophy (e.g. Wilson et al, 2014aWilson et al, , 2016. The present study does not resolve the tension between these two literatures.…”
Section: Anterior Frontal and Anterior Temporal Regionscontrasting
confidence: 99%
“…Yet, along-side many of the findings just reviewed, our results stand in contrast to the apparent stability of compositional processes following anterior temporal atrophy (e.g. Wilson et al, 2014aWilson et al, , 2016. The present study does not resolve the tension between these two literatures.…”
Section: Anterior Frontal and Anterior Temporal Regionscontrasting
confidence: 99%
“…Tyler et al, 2010;Rogalsky et al, 2018) raising the question of the role of anterior regions in syntactic processing (e.g. Thothathiri et al, 2012;Magnusdottir et al, 2013;Blank et al, 2016;Wilson et al, 2016;Fedorenko et al, 2018;Rogalsky et al, 2018). Matchin and Hickok (2019) propose that the inherently different processing requirements for language production and comprehension account for the differences in syntactic processing related neural substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we addressed the question of whether impairments producing the content and structure of spontaneously generated speech are related to different patterns of focal brain damage. Whether unique brain regions are required to produce content and structure during connected speech speaks to a central debate concerning the specificity of brain regions required for syntactic processing (e.g., Wilson and Saygın, 2004;Thothathiri et al, 2012;Magnusdottir et al, 2013;Blank et al, 2016;Wilson et al, 2016;Fedorenko et al, 2018;Rogalsky et al, 2018; cf. Dapretto and Bookheimer, 1999;Hagoort and Indefrey, 2014;Friederici et al, 2017).…”
Section: The Current Studymentioning
confidence: 99%
“…Another fMRI study showed greater left inferior frontal activation during grammatically complex sentences compared with simple sentences in controls, whereas patients with naPPA did not show a difference in left inferior frontal activation for these two types of sentences (Wilson et al 2010a). In a more recent study, recruitment of a broad, left hemisphere language network was particularly disrupted in patients with grammatical comprehension difficulty due to naPPA (Wilson et al 2016). Such findings suggest that the language impairment in naPPA is due in part to disruption of large-scale perisylvian neural networks that support language processing.…”
Section: Nonfluent/agrammatic Primary Progressive Aphasiamentioning
confidence: 93%